2013
DOI: 10.1177/1754073912468298
|View full text |Cite
|
Sign up to set email alerts
|

Comment: The Appraising Brain: Towards a Neuro-Cognitive Model of Appraisal Processes in Emotion

Abstract: Appraisal theories have described elaborate mechanisms underlying the elicitation of emotion at the psychological-cognitive level, but typically do not integrate neuroscientific concepts and findings. At the same time, theoretical developments in appraisal theory have been pretty much ignored by researchers studying the neuroscience of emotion. We feel that a stronger integration of these two literatures would be highly profitable for both sides. Here we outline a blueprint of the "appraising brain." To this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 43 publications
4
74
1
Order By: Relevance
“…We have recently begun a line of research aimed at outlining the neurocognitive mechanisms underlying appraisal processes (Brosch & Sander, 2013a) and linking the concept of core values to neuroeconomic valuation and decision research (Brosch, Coppin, Scherer, Schwartz, & Sander, 2011;Brosch, Coppin, Schwartz, & Sander, 2012;Brosch & Sander, 2013b). In one fMRI study, we had participants with varying core value hierarchies participate in a donation task where they were asked to distribute a financial amount between themselves and a charitable organization (Brosch et al, 2011).…”
mentioning
confidence: 99%
“…We have recently begun a line of research aimed at outlining the neurocognitive mechanisms underlying appraisal processes (Brosch & Sander, 2013a) and linking the concept of core values to neuroeconomic valuation and decision research (Brosch, Coppin, Scherer, Schwartz, & Sander, 2011;Brosch, Coppin, Schwartz, & Sander, 2012;Brosch & Sander, 2013b). In one fMRI study, we had participants with varying core value hierarchies participate in a donation task where they were asked to distribute a financial amount between themselves and a charitable organization (Brosch et al, 2011).…”
mentioning
confidence: 99%
“…An important next research step will be to link individual appraisal structures and emotions not only to intentions to reduce energy use, but also to objective measures of actual behavior (e.g., actual energy use). At the conceptual level, psychological and neuroimaging research has shown that the appraisal process occurs very rapidly and in a partially automatic fashion (Grandjean and Scherer, 2008;Brosch and Sander, 2013a). Thus, not all aspects of the appraisal process are necessarily accessible to introspection and can be reported in a questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Normative models such as the VBN already include core values, which play an important role in the elicitation of emotions (Nelissen et al, 2007;Brosch and Sander, 2013a) and their role in decision-making (Brosch and Sander, 2013b), as well as moral emotions such as guilt or shame that serve to motivate the normative function of social constraints. In this perspective, environmental-friendly behavior seems to be conceptualized as "morally correct" behavior, that is, people save energy to avoid violating a social norm, resulting in real or imagined social disapproval and feelings of guilt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations